Gender Equality in Mosque Management: Women's Involvement in Masjid Raya Mujahidin Pontianak - Cucu Nurjamilah (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
In the context of da’wah management, the functions of the mosque are not optimal yet. The activities of the masjid are only focused on the center of worship, religious activities, but have not touched the equality yet. In order to answer the problems above, the researcher used fieldwork with the method of case studies. Through an in-depth interview technique, participant observation and study of documentation found that Masjid Mujahidin Pontianak has involved women in the management of masjid, and succeeded in increasing the functions of a mosque. Involving women in the management of mosque will strengthen one dimension that is important in Islam that is Islam seriously upholds the equality of degree in various aspect, including Islam is a religion that highly responsive gender. When the management of mosque is filled with a variety of different groups, including giving places to women, then frictions and clashes caused by differences in the understanding in the society will be minimized, and then the role and function of masjid will be able to touch various aspects such as economics, health, and education.